Religion, Economy, and State in Ottoman-Arab History - Ochsenwald, William (Analecta Isisiana: Ottoman and Turkish Studies, 2010)
A collection of articles on the Hijaz, Yemen and other parts of the Ottoman Arab world in the nineteenth and twentieth centuries